2021
DOI: 10.1002/pbc.28991
|View full text |Cite
|
Sign up to set email alerts
|

Association of psychological distress and religious coping tendencies in parents of children recently diagnosed with cancer: A cross‐sectional study

Abstract: Purpose: Parents of children with cancer exhibit high levels of psychological distress.Parents of children with serious illness report religion and spirituality are important coping resources. We sought to describe characteristics of religion, religious coping, social support, and resiliency in parents of children newly diagnosed with cancer and examine associations between psychological distress and self-reported religious coping, religiosity, resiliency, and social support. Patients and methods: Cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
(93 reference statements)
0
5
0
2
Order By: Relevance
“…Other investigators have observed that Islamic beliefs and practices may have a communal effect, with parents reporting higher perceived support in medically complex children (23). Recognising these unique coping strategies emphasizes the importance and the need for healthcare providers to provide culturally sensitive care in supporting families after PICU discharge, noting that negative religious coping was associated with a higher level of psychological distress in parents of children with cancer (24). By understanding the preference for the use of religious and spiritual practices, healthcare providers can effectively assist parents on their journey to their child's recovery (25).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have observed that Islamic beliefs and practices may have a communal effect, with parents reporting higher perceived support in medically complex children (23). Recognising these unique coping strategies emphasizes the importance and the need for healthcare providers to provide culturally sensitive care in supporting families after PICU discharge, noting that negative religious coping was associated with a higher level of psychological distress in parents of children with cancer (24). By understanding the preference for the use of religious and spiritual practices, healthcare providers can effectively assist parents on their journey to their child's recovery (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, the negative forms of Turning to religion strategy work the opposite way leading to focusing on tension and continuous sense of struggling with guilt and punishment. Dolan et al [ 39 ] emphasize the need of potential screening tests aimed at detecting and responding to negative religious attitudes. Substance use was, in turn, the least common strategy among all parents, although it was significantly more frequently chosen by fathers.…”
Section: Discussionmentioning
confidence: 99%
“…The data that was found in the articles highlighting the negative aspects of R/S are important to be considered and an indication that healthcare professionals and chaplains must be aware of them. Negative religious coping can lead to poorly adaptive coping strategies that increase psychological distress (Dolan et al, 2021) and, consequently, interfere with the quality of life and the occurrence of psychopathological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, vulnerable parents may experience increased anxiety that stems from their feelings of being punished by God or the divine (Dolan et al, 2021). In this way, this negative religious/spiritual coping represents struggles in the person's relationship with God and/or religious community and includes strategies such as the reassessment of the punishing God (McGrady et al, 2021).…”
Section: Discussionmentioning
confidence: 99%